HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN OTOT LENGAN DENGAN KEMAMPUAN SHOOTING TIM BASKET SMA N 12 PEKANBARU - Sepdiandri Ahmad Putra; Drs. Saripin, M.Kes, AIFO '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study was to determine the relationship of leg muscle explosive power and muscular arms with the shooting ability of high school basketball team 12 Pekanbaru. This type of research is using correlation analysis, survey method, and samples were not separated. The population in this study were all high school basketball team 12 Pekanbaru. The sampling technique in this study using purposive sampling or also known as sampling considerations. So researchers set of samples in this study were students of class X and XI numbered 10 people. Results of analysis showed that there is a relationship of leg muscle explosive power and muscular arms with the shooting ability of high school basketball team 12 Pekanbaru, with r = 0.779> rtabel = 0.632.Keywords: Explosive Power leg muscles, arm muscles, Shooting, Basketball